2001
DOI: 10.7164/antibiotics.54.1054
|View full text |Cite
|
Sign up to set email alerts
|

Tripropeptins, Novel Antimicrobial Agents Produced by Lysobacter sp. I. Taxonomy, Isolation and Biological Activities.

Abstract: Peptide antibiotics tripropeptins A, B, C, D and Z were isolated from cultured cells and broth of Lysobacter sp. The differences among these components are in the lengths of the alkyl side chain. Tripropeptins are active against Gram-positive bacteria including MRSA in vitro. Bactericidal activity of tripropeptin C disappeared in the simultaneous presence of chloramphenicol, a bacteriostatic agent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
61
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(62 citation statements)
references
References 0 publications
1
61
0
Order By: Relevance
“…Our experiments therefore revealed that TPPC exhibits potent activity against the drug-resistant pathogens MRSA and VRE both in vivo and in vitro. In our experiments, clinically isolated strains, including MRSA, VRE, and penicillin-resistant Streptococcus pneumoniae, showed no resistance to TPPC (4,5), indicating that TPPC has a unique mode of action.…”
Section: In Vitro and In Vivo Activities Of Tppcmentioning
confidence: 58%
See 3 more Smart Citations
“…Our experiments therefore revealed that TPPC exhibits potent activity against the drug-resistant pathogens MRSA and VRE both in vivo and in vitro. In our experiments, clinically isolated strains, including MRSA, VRE, and penicillin-resistant Streptococcus pneumoniae, showed no resistance to TPPC (4,5), indicating that TPPC has a unique mode of action.…”
Section: In Vitro and In Vivo Activities Of Tppcmentioning
confidence: 58%
“…TPPC was isolated by the method reported previously (4). VAN was purchased from Shionogi (Osaka, Japan).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…5A). Although the structure of tripropeptin A has been known for more than a decade (Hashizume et al, 2001, Hashizume et al, 2004, genetic analysis of its biosynthesis was only recently reported (Medema et al, 2014). Our study revealed that three NRPS genes trpA, trpB, trpC are organized in a single-operon (Fig.…”
Section: Lipopeptidesmentioning
confidence: 68%